Modern methods of diagnosing periodontal tissue diseases in the concept of a systemic approach to treatment. (Literature review. Part 2) - Symonenko, Р. В.; Etnis, Л. О. (Actual Dentistry, 2024)
Resume. Diagnostics is one of the most urgent tasks of modern medicine, the latest achievement of which inspire the for new methods of detecting and predicting the course of diseases. Careful diagnosis is the key to successful prevention and treatment of such an extremely common and complex disease as periodontitis. The diagnosis of periodontitis includes several stages and has different levels of research depth, which in practice strongly depends on the professional training of the doctor, the capabilities of the clinic, the availability of the laboratory and the motivation of the patient. But, despite the wide possibilities, all diagnostic, treatment and preventive activities of the doctor are related to forecasting, timely prediction of complications, possible development of disease relapses. Therefore, implementation of the system of diagnostic monitoring with the definition of predictors of disease, its biological markers, criteria for evaluating its course, forecasting possible results and the effectiveness of treatment measures is absolutely necessary. From this point of view, the development of laboratory methods and the possibility of their application in the diagnostics of periodontal diseases is a very urgent problem and requires not only technical perfection, but also considering the peculiarities of the etiopathogenesis of oral cavity lesions. The optimal choice of biomarkers is closely related to the choice of the source and method of sampling the material for diagnostics. Based on the requirements for an ideal biomarker, saliva, gingival fluid (GCF), peri-implant sulcus fluid (PISF) and residual mouthwash can be reliable sources of biomarkers in the oral cavity. Our review of foreign literature describes the following biomarkers contained in oral fluids: interleukin 1-beta (IL 1_), interleukin 6 (IL-6) and matrix metalloproteinase-8 (MMP8). The advantages and disadvantages of such immuno biochemical methods for determining the level of biomarkers as immunoblotting and enzyme-linked immunosorbent assay (ELISA) were also analyzed. Given that biomarkers can be used as a basis for early detection of periodontal diseases, prediction of further progression and response to treatment, their use can provide better treatment planning, particularly with the use of a personalized approach, and a stable positive outcome, even in patients with complex general somatic pathologies.